University Interaction with Regional Subjects in the Assessments of the Faculty - M. V. Boguslavsky; N. V. Ladyzhets; O. V. Sannikova; E. V. Neborsky (Moscow Polytechnic University, 2020)
The article was prepared on the basis of a field study implemented at Udmurt State University as a part of the research project "Transitive University in the Face of Global, National, and Regional Challenges". The article considers the results of a survey related to the assessment by the teaching staff of the ways of interacting with regional subjects of the social order. 75% of respondents acknowledge the risks associated with educational and labor migration of young people from the Udmurt Republic. Professors mainly form competencies within the framework of the regular educational process: they select the topics of students' term papers and graduate work in accordance with the needs of the region, take into account the needs of the labor market in the content of classes, participate in the organization of practices and help students to find employment in the regional labor market. According to professors, the most important role of the university is to participate in the development of the region along with large organizations and branches of government. A cooperative approach prevails, in which the university plays the role of a partner, not a driver. Professors rated the interaction of the university administration with state authorities of the Udmurt Republic as satisfactory - the average score was 3.1 points out of 5. Prospects for the development of the university are seen by the professors in four directions: orientation to the regional labor market, interaction with employers; scientific and innovative activities; digitalization and informatization of educational and administrative processes; development of international cooperation. Pessimism prevails in the responses of professors about the hopes for cooperation with authorities and business in the region, which requires a separate study, since it can be caused by a number of factors. As suggestions to the leadership of the university, the professors indicated: the need for more active interaction between the university administration and the leadership of the region and business, involving the university in regional projects, identifying the needs of the region and stimulating the leadership of institutions to form new directions in the scientific and educational sector, taking into account the prospects for the development of the republic. The study revealed two obvious facts. Firstly, professors are aware of the important role of the university and even support this idea as a strategic one. In other words, they show willingness. Secondly, professors, most likely, expect the initiative of active interaction with the labor market and regional authorities from the leadership of the university. In other words, they do not translate preparedness into action, awaiting action on the part of management.